The meaning of 'indecency' under the Law of Indecent Assault - Mohamad Yunus, Mohamad Ismail (LexisNexis, 2016)
On 25 May 2015, a former Malaysian defence attaché Muhammad Rizalman Ismail, claimed trial at the New Zealand High Court on the charge of indecent assault. His case was set for case management in August 2014, reported One News, New Zealand. On 09 May 2014, the accused was literally caught with his pants down while he was touching Tania Billingsley, the complainant in her bedroom in the Wellington suburb of Brooklyn, New Zealand. On 24 October 2014, Rizalman returned to New Zealand after the Malaysian Government received a formal extradition request from the New Zealand Government. He later appeared in the Wellington District Court on 27 October 2014 and was granted bail. On 21 November 2014, Rizalman pleaded not guilty to the charge he was facing. He returned to court to face trial on 19 February 2015. It was reported that Rizalman would be tried before the High Court in Wellington on November 2015.